2015
DOI: 10.1136/archdischild-2015-308558
|View full text |Cite
|
Sign up to set email alerts
|

Integrating primary and secondary care for children and young people: sharing practice

Abstract: ObjectiveTo share innovative practice with enough detail to be useful for paediatricians involved in planning services.DesignA review of practice, adopting a realist approach.SettingWe collected detailed information about five initiatives which were presented at two meetings in July and October 2014 and telephone interviews between July and November 2014 with key informants, updating information again in February 2015.ResultsThe five case studies involved three clinical commissioning groups (CCGs): Islington C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…Just one study 76 suggested that MDTs encourage family and carer support for patient care. In five instances of MDT initiatives in the UK, enhanced access strategies of telephone MDT, Hospital at Home, and Advice and Guidance services produced better patient experience and less inconvenience and disruption for patients and families, and gave them extra skills and confidence to look after their unwell child without professional support.…”
Section: Causal Link 3:5 -Multidisciplinary Team Supports Voluntary Imentioning
confidence: 99%
See 4 more Smart Citations
“…Just one study 76 suggested that MDTs encourage family and carer support for patient care. In five instances of MDT initiatives in the UK, enhanced access strategies of telephone MDT, Hospital at Home, and Advice and Guidance services produced better patient experience and less inconvenience and disruption for patients and families, and gave them extra skills and confidence to look after their unwell child without professional support.…”
Section: Causal Link 3:5 -Multidisciplinary Team Supports Voluntary Imentioning
confidence: 99%
“…[86][87][88] It also shifts providers' expectations for communication and increases their awareness of the importance and benefits of involving other primary care providers in complex cases, 89 upskills primary care providers and promotes shared responsibility. 76 A narrative case study of mental health integration in a CCM showed that this co-support across disciplinary boundaries helps members of each profession not to feel alone in the face of complex multimorbidity issues about which they are not specialists and to make shared decisions on complex problems. 66 …”
Section: Causal Link 3:7 -Co-support and Decision-makingmentioning
confidence: 99%
See 3 more Smart Citations